Targeting ferroptosis: a promising strategy to overcome drug resistance in breast cancer - Peng, Cuixin; Chen, Yanning; Jiang, Mingzhang (Frontiers in Oncology, 2024)
Breast cancer is one of the most prevalent malignancies affecting women worldwide, with its incidence increasingly observed in younger populations. In recent years, drug resistance has emerged as a significant challenge in the treatment of breast cancer, making it a central focus of contemporary research aimed at identifying strategies to overcome this issue. Growing evidence indicates that inducing ferroptosis through various mechanisms, particularly by inhibiting System Xc-, depleting glutathione (GSH), and inactivating glutathione peroxidase 4 (GPX4), holds great potential in overcoming drug resistance in breast cancer. It is anticipated that therapies targeting ferroptosis will emerge as a promising strategy to reverse tumor resistance, offering new hope for breast cancer patients. This review will explore the latest advancements in understanding ferroptosis in the context of breast cancer drug resistance, with a particular emphasis on the roles of ferroptosis inducers and inhibitors, and the impact of ferroptotic pathways on overcoming drug resistance in breast cancer.